2010
DOI: 10.1089/gtmb.2009.0175
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis for a Novel Splice Mutation of PHEX Gene in a Large Han Chinese Family Affected with X-Linked Hypophosphatemic Rickets

Abstract: A novel splice mutation c.849+1G>A in the PHEX gene is responsible for XLH in the studied family. Further studies may enhance our understanding of the role of this mutation in the pathogenesis of XLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The predicted loss of the extracellular and zinc-binding domains of the mutation disrupts the overall integrity of the PHEX protein, which may lead to loss of protein function and hence leads to XLHR (Gaucher et al, 2009;Qiu et al, 2010;Kang et al, 2012). Mutation of the female patient (II:1) is thought to be a de novo mutation as none of her parents (I:1 and I:2) had any clinical evidence for HR, consistent with that de novo mutation is more frequent in females than males (Durmaz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The predicted loss of the extracellular and zinc-binding domains of the mutation disrupts the overall integrity of the PHEX protein, which may lead to loss of protein function and hence leads to XLHR (Gaucher et al, 2009;Qiu et al, 2010;Kang et al, 2012). Mutation of the female patient (II:1) is thought to be a de novo mutation as none of her parents (I:1 and I:2) had any clinical evidence for HR, consistent with that de novo mutation is more frequent in females than males (Durmaz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…reported that total procedure‐related loss rate was 2.3%: 1.6% intrauterine foetal deaths within 48 h of the procedure and 0.7% spontaneous abortions in the 2 weeks following the procedure . However, there is almost no procedure‐related abortion and foetal death in Chinese study and previous studies have shown that prenatal diagnosis by percutaneous umbilical blood sampling is safe . Moreover, it would provide us with the neutrophils needed for the DHR analysis.…”
Section: Discussionmentioning
confidence: 89%
“…According to the PHEX mutation database, the frequencies of the different types of mutations include the following: 27% frameshifts, 19.8% abnormal splicing, 19.4% missense, 18% nonsense, 28% deletions, and 2.4% polymorphisms. However, only 14 mutations (2 deletion mutation, 3 nonsense mutations, 1 frameshift mutation, 3 donor splice site mutations, and 5 missense mutations) in the PHEX gene have been reported in Chinese patients with familial XLH [15][20]. In this study, we identified PHEX gene mutations in Chinese patients (familial and sporadic) with hypophosphatemic rickets/osteomalacia in order to elucidate the PHEX gene mutation types and clinical features observed in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%